Exploring spatial and temporal variations in methane emissions from rice paddies - Shang-Hung Pao; Huey-Lin Lee; Chiao-Wen Lin; Wei-Jen Lin; Hsing-Juh Lin (European Journal of Agronomy, 2026)

Species-specific greenhouse gas emissions and carbon budgets in freshwater monoculture ponds - Zhao-Jun Yong; Wei-Jen Lin; Yao-Chen Lee; Yen-Cheng Liang; Shuenn-Der Yang; Hsing-Juh Lin (Aquaculture International, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Freshwater clam aquaculture could turn inland ponds from carbon sinks into carbon sources - Wei-Jen Lin; Chien-Hsing Chiang; Chih-Chiang Tsai; Takeshi Chijimatsu; Hsing-Juh Lin (Hydrobiologia, 2026)

Dexmedetomidine Mitigates Sevoflurane-Induced Neurodevelopmental Effects in Paediatric Anaesthesia: A Meta-Analysis and Preclinical Study - Hsuan-Chih Lao; Chia-Wei Huang; Ssu-Han Wang; Yen-Lin Su; Chien-Hui Chang; Cheng-Yen Liao; Jen-Chieh Wu; Ying-Chun Lin; Jin-Wu Tsai (Journal of Neuroimmune Pharmacology, 2026)
Sevoflurane (Sevo) anaesthesia in children is linked to an increased incidence of postoperative emergence agitation (EA) and potential neurotoxicity in developing brains. However, the specific risks of subanaesthetic foetal or neonatal exposure to Sevo remain unclear. This study evaluates the safety and efficacy of combining dexmedetomidine (Dex) with Sevo to manage EA in paediatric anaesthesia. A systematic review and meta-analysis of randomized controlled clinical trials involving children under 8 years old revealed that Dex significantly reduces EA incidence when administered via intravenous, perineural, and intranasal routes. Using in utero electroporation, we found that pregnant mice exposed to 2.5% Sevo at embryonic days 14.5 and 15.5 exhibited transient neuronal migration deficits, with 25% of neurons delayed in deeper cortical layers. However, these neurons migrated to the cortex by postnatal day 8. Neonatal mice exposed to 2.5% Sevo experienced a 10% reduction in dendritic spine density in adolescence, associated with impaired somatosensory function, as assessed by the Von Frey test. Remarkably, Dex pretreatment ameliorated these pathological and functional changes. Thus, foetal or neonatal Sevo exposure can delay neuronal migration and reduce dendritic spine density. Dex co-administration effectively mitigates these adverse outcomes, supporting its potential use in paediatric anaesthesia to protect developing brains. Graphical abstract

Identification and quantification of per- and polyfluoroalkyl substances in wastewater from Taiwan using targeted and non-targeted approaches - Jen-Yi Hsu; Chih-Wei Chang; Yu-Wen Lin; Yuan-Chih Chen; Pao-Chi Liao (Chemosphere, 2025)

Pilot study on integrating multidisciplinary technologies to implement an autonomous and smart harvester for asparagus - Joe-Air Jiang; Jen-Cheng Wang; Hung-Jen Lin; Cheng-Ying Chou; Chia-Chun Chien; Wei-Hao Huang; An-Chi Liu; Cheng-Chun Lee; Ming-Chi Guo; Jui-Chu Peng (Computers and Electronics in Agriculture, 2025)

Climate zone governs mercury fate along forest hydrological pathways - Weibin Ma; Jen-How Huang; Gunnar Lischeid; Nantao Liu; Longyu Jia; Fei Wu; Meiqing Sun; Ming Lei; Luxiang Lin; Zhiyun Lu; Wei Yuan; Xun Wang; et al. (Journal of Hazardous Materials, 2025)

Correction: Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Seismic behavior of innovative precast hybrid steel-concrete beam-column connections - Chien-Chung Chen; Hung-Jen Lee; Yi-Yao Zhao; Yin-Nan Huang; Chiu-Huang Lin; Hsiao-Wei Chan (Engineering Structures, 2025)

Rain gardens can be combined with urban planning strategies to increase urban resilience - Chi-Feng Chen; Yi-Wei Chen; Jen-Yang Lin (Landscape and Ecological Engineering, 2025)

Community metabolism and greenhouse gas emissions in abandoned tropical salt pans - Shu-Yen Huang; Wei-Jen Lin; Li-Hua Lee; Hsing-Juh Lin (Estuarine, Coastal and Shelf Science, 2025)

Biomass energy for a sustainable Taiwan: Technologies, policies, and future prospects - Yu-Wei Lin; Yu-Ting Liu; Li-Cheng Huang; Shing-Chou Lin; Shean-Jen Chen; YongMan Choi (Biomass and Bioenergy, 2025)

Predicting and regulating potential zone for heavy metal re-contaminated farmland: Case study in Taiwan - Jieh-Haur Chen; Mu-Chun Su; Meng-Fen Yeh; Wei-Jen Lin; Tzuyang Yu; Ming-Chung Yeh (Environmental Development, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

The Deep Space Radiation Probe: Development of a first lunar science payload for space environment studies and capacity building - Loren C. Chang; Wei-Yi Lin; Yi-Hsuan Chou; Jen-Siang Lin; Chieh Lung; I. Chen; Kai-Jie Hou; Glenn Franco Gacal; Yi-Chung Chiu; Yushun Wang; Hui-Hui Chou; Chi-Kuang Chao; et al. (Advances in Space Research, 2025)

Enhanced electrocatalytic conversion of CO2 to CO via a non-stoichiometric zinc-fluorine amorphous interface - Hsin-Chiao Wu; Chia-Chen Lin; Chu-Hsin Yang; Yu-Wei Huang; Chen-Hao Yeh; Yu-Jen Chou; Ta-Chung Liu (Chemical Engineering Journal, 2025)

Allopatric Speciation and Interspecific Gene Flow Driven by Niche Conservatism of Diploderma Tree Lizards in Taiwan - Tzong‐Han Lin; Zong‐Yu Shen; Ming‐Hsun Chou; Pei‐Wei Sun; Chin‐Chia Shen; Jen‐Pan Huang; Si‐Min Lin (Molecular Ecology, 2025)
Allopatric speciation is a widely accepted hypothesis for species distributed across geographic barriers. Meanwhile, niche conservatism, the tendency of species to retain their ancestral ecological traits, helps reinforce genetic differentiation by stabilising species distributions over time and reducing the role of competition in shaping range boundaries. In contrast, hybridisation can occur at the edges of distribution after secondary contact following climatic or geological events, leading to a reduction in genetic divergence between divergent lineages. In this study, we investigated the role of geographic barriers, niche conservatism and gene flow in the speciation history of Diploderma species in Taiwan, where geographically distinct taxa share similar environmental preferences. By using ddRAD‐seq data, seven distinct genetic clusters were identified with two putatively new cryptic species in D. brevipes and D. polygonatum . Most sister species pairs share similar climatic niches based on niche equivalency and similarity tests. We further detected significant historical gene flow between lineages of D. brevipes and D. polygonatum , where secondary contact might have occurred because of palaeoclimate changes and historical demographic expansion. Our results demonstrate that niche conservatism does not always act in concert to strengthen the result of allopatric speciation; instead, it may also lead to gene flow between divergent lineages following secondary contact. On the other hand, postdivergence gene flow may be a creating force generating phenotypic diversity in sexually selected traits in our study system. The underestimated species diversity of Diploderma in Taiwan requires further taxonomic work in the future.

Indoxyl Sulfate Induces Ventricular Arrhythmias Attenuated by Secretoneurin in Right Ventricular Outflow Tract Cardiomyocytes - Yuan Hung; Chen-Chuan Cheng; Yen-Yu Lu; Shih-Yu Huang; Yao-Chang Chen; Fong-Jhih Lin; Wei-Shiang Lin; Yu-Hsun Kao; Yung-Kuo Lin; Shih-Ann Chen; Yi-Jen Chen (Cardiovascular Toxicology, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

A sensitive post-column derivatization approach for enhancing hydroxyl metabolites detection - Yen-Chu Lin; Shiu-Wen Huang; San-Yuan Wang; Jing-Rong Su; Jimmy Junxiang Wang; Ming-Jen Hsu; Hsiao-Wei Liao (Analytica Chimica Acta, 2025)

Carbonate precipitation-derived CO2 outgassing offsets the mineral weathering sink in the orogenic regime of southwestern Taiwan: Insights from triple Sr isotopes - Hou-Chun Liu; Yun-Cian Lin; Yan-Hong Chen; Meng-Xuan Li; Chen-Feng You; Kuo-Fang Huang; Wei-Jen Huang; Hung-Chun Chao (Science of The Total Environment, 2024)

Field performance of 15 rain gardens in different cities in Taiwan - Chi-Feng Chen; Yi-Wei Chen; Cheng-Han Lin; Jen-Yang Lin (Science of The Total Environment, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Flushing emissions of methane and carbon dioxide from mangrove soils during tidal cycles - Chiao-Wen Lin; Wei-Jen Lin; Chuan-Wen Ho; Yu-Chen Kao; Zhao-Jun Yong; Hsing-Juh Lin (Science of The Total Environment, 2024)

Biophysical mechanisms underlying tefluthrin-induced modulation of gating changes and resurgent current generation in the human Nav1.4 channel - Hsing-Jung Lai; Ming-Jen Lee; Hsin-Wei Yu; Kuan-Wen Chen; Ke-Li Tsai; Pi-Chen Lin; Chiung-Wei Huang (Pesticide Biochemistry and Physiology, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Cobalt and zinc imidazolate encapsulated in reduced graphene oxide and the derived nitrogen-enriched carbon frameworks (CoNC@rGO) for electrochemically sensing acetaminophen (APAP) - Yu-Jen Shih; Sheng-Kai Lin; Zhi-Lun Wu; Wei-Hsiang Chen (Chemical Engineering Journal, 2024)

Anthropogenic nitrogen pollution inferred by stable isotope records of crustose coralline algae - Aafaq Nazir; Chiao-Feng Lai; Shih-Wei Wang; Showe-Mei Lin; Hong-Chun Li; Ming-Tsung Chung; Pei-Ling Wang; Yung-Che Tseng; Jen-Chieh Shiao (Marine Pollution Bulletin, 2024)

Mangrove carbon budgets suggest the estimation of net production and carbon burial by quantifying litterfall - Wei-Jen Lin; Chiao-Wen Lin; Hsin-Hsun Wu; Yu-Chen Kao; Hsing-Juh Lin (CATENA, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

Copper nanoparticles encapsulated in reduced graphene oxide electrode (CuxrGO1-x) for the electrochemical quantification of metformin in water - Yu-Jen Shih; Yu-Qiao Su; Wei-Hsiang Chen; Sheng-Kai Lin; Yi-Chun He; Chin-Pao Huang (Chemical Engineering Journal, 2023)

Ethanol production using the whole solid-state fermented sugarcane bagasse cultivated by Trichoderma reesei RUT-C30 supplemented with commercial cellulase - Ching An Lin; Cheng Cheng; Li Wei Chen; C. Will Chen; Kow Jen Duan (Biocatalysis and Agricultural Biotechnology, 2023)

Genomic architecture underlying morphological and physiological adaptation to high elevation in a songbird - Chia‐Wei Lu; Shih‐Ting Huang; Shun‐Jen Cheng; Chen‐Tau Lin; Yu‐Cheng Hsu; Cheng‐Te Yao; Feng Dong; Chih‐Ming Hung; Hao‐Chih Kuo (Molecular Ecology, 2023)
Organisms often acquire physiological and morphological modifications to conquer ecological challenges when colonizing new environments which lead to their adaptive evolution. However, deciphering the genomic mechanism of ecological adaptation is difficult because ecological environments are often too complex for straightforward interpretation. Thus, we examined the adaptation of a widespread songbird—the rufous‐capped babbler ( Cyanoderma ruficeps )—to a relatively simple system: distinct environments across elevational gradients on the mountainous island of Taiwan. We focused on the genomic sequences of 43 birds from five populations to show that the Taiwan group split from its sister group in mainland China around 1–2 million years ago (Ma) and colonized the montane habitats of Taiwan at least twice around 0.03–0.22 Ma. The montane and lowland Taiwan populations diverged with gene flow between them, suggesting strong selection associated with different elevations. We found that the montane babblers had smaller beaks than the lowland ones, consistent with Allen's rule, and identified candidate genes— COL9A1 and SOX11 —underlying the beak size changes. We also found that altitudinally divergent mutations were mostly located in noncoding regions and tended to accumulate in chromosomal inversions and autosomes. The altitudinally divergent mutations might regulate genes related to haematopoietic, metabolic, immune, auditory and vision functions, as well as cerebrum morphology and plumage development. The results reveal the genomic bases of morphological and physiological adaptation in this species to the low temperature, hypoxia and high UV light environment at high elevation. These findings improve our understanding of how ecological adaptation drives population divergence from the perspective of genomic architecture.

Modeling of an integrated H2S/NH3 scrubber and regeneration columns for coke oven gas purification - Hao-Jen Pan; Ming-Chun Fang; Jeffrey D. Ward; Hao-Yeh Lee; Hsun-Yu Lin; Cheng-Ting Hsieh; Chih-Lung Lee; Tzu-Hsien Huang; Yu-Chen Hsieh; Shih-Chieh Lin; Wei-Ti Chou (Journal of Cleaner Production, 2023)

Editorial: Oceanographic processes linking nearshore, continental shelf, and shelf break - Feng-Hsun Chang; Yun-Chi Lin; Kuo-Ping Chiang; Ya-Han Nien; Chih-hao Hsieh; Wei-Jen Chen; Chin-Chang Hung; Toru Kobari; Hiroaki Saito; William Savidge (Frontiers in Marine Science, 2023)

Lightweight Flexible Polyimide-Derived Laser-Induced Graphenes for High-Performance Thermal Management Applications - Yu-Sheng Hsiao; Cai-Wan Chang-Jian; Tzu-Yen Huang; Ying-Lin Chen; Chung-Wei Huang; Jen-Hsien Huang; Nian-Jheng Wu; Shih-Chieh Hsu; Chih-Ping Chen (Chemical Engineering Journal, 2023)

Mercury cycling and isotopic fractionation in global forests - Xun Wang; Wei Yuan; Che-Jen Lin; Xinbin Feng (Critical Reviews in Environmental Science and Technology, 2022)

Biomechanical Effects of Bone Atrophy, Implant Design, and Vertical or Tilted of Posterior Implant on All-on-Four Concept Implantation: Finite Element Analysis - Heng-Li Huang; Ting-Wei Lin; Hui-Ling Tsai; Yu-Ling Wu; Aaron Yu-Jen Wu (Journal of Medical and Biological Engineering, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Habitat change and its consequences on reef fish specialization in biogeographic transition zones - Yuting Vicky Lin; Wanchien Victoria Hsiao; Wei‐Jen Chen; Vianney Denis (Journal of Biogeography, 2022)
Aim Reef fishes are commonly recognized as sentinels of the ongoing tropicalization in biogeographic transition zones between temperate and tropical areas. Despite the reliance of these marine ectotherms on the benthos, the importance of benthic habitat has rarely been considered as a factor constraining fish distribution. Therefore, our study aims at examining the consequences of both temperature and benthic variations on the fish fauna and diagnosing potential sentinels of these environmental changes. Location Taiwan, West Pacific. Taxon Teleostei (184 species). Methods We examined how the partitioning of habitats can influence the specialization of fish fauna along a latitudinal gradient. We diagnosed ‘specialist’ and ‘generalist’ fishes in this partitioning. For each specialist, we further evaluated whether its distribution is constrained by temperature, benthic habitat or both factors combined. The change in sea surface temperature over the last three decades was also monitored. Results Fish fauna showed the highest specialization when tropical and subtropical partitions of habitat were considered. Fifty‐one tropical specialists, 7 subtropical specialists and 21 possible generalists were identified. Among specialists, 13 species were associated with temperature, 19 with habitat and 26 with both factors. Steady warming occurred across latitudes, but was accentuated in the winter of subtropical habitat. Main Conclusions Our results suggested that the distribution of some specialist fishes was constrained only by temperature while the distribution of some others also depended on the availability of benthic habitats. Consequently, under global warming, the distribution of some specialists might shift in a manner that follows the movement of isotherms, while the distribution of others might also be conditioned by the poleward shifts of benthos. A temporal mismatch between the emergence of suitable thermal environments and the arrival of some specialists may exist. Therefore, the tropicalization of high‐latitude areas may be characterized by different waves of colonization.

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Realization of Natural Human Motion on a 3D Biped Robot For Studying the Exoskeleton Effective - Chi-Ying Lee; Shih Chieh Lan; Jung-Ji Lin; Yu-Ting Lin; Po-Shen Chiang; Wei-Li Hsu; Kuo-Kuang Jen; Andy Y. S. Huang; Jia-Yush Yen (Journal of Medical and Biological Engineering, 2021)

Effect of dermal phthalate levels on lung function tests in residential area near a petrochemical complex - Chih-Wen Wang; Szu-Chia Chen; Da-Wei Wu; Huang-Chi Chen; Hung-Hsun Lin; Hung Su; Jen-taie Shiea; Wen-Yi Lin; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Science and Pollution Research, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Effects of Sediment Characteristics on Carbon Dioxide Fluxes Based on Interacting Factors in Unvegetated Tidal Flats - Wei-Jen Lin; Ming-Chih Chiu; Chiao-Wen Lin; Hsing-Juh Lin (Frontiers in Marine Science, 2021)
The contribution of unvegetated tidal flats to global net primary production is comparable to that of some vegetated coastal habitats. However, compared to carbon flux regulating factors in vegetated habitats, those in unvegetated tidal flats are not well understood, particularly in terms of their cause-effect relationships. Maximum gross primary production (GPP m ), net primary production (NPP) and total respiration (TR) during emersion at noon when the irradiance level was at the saturation level for photosynthesis in nine unvegetated tidal flats across the Taiwan Strait in tropical and subtropical regions were determined in winter and summer from 2011 to 2016 to examine the direct and indirect relationships between sediment characteristics and carbon fluxes by using structural equation models (SEM). Most of the GPP m and NPP values were higher in winter than in summer. Conversely, the TR values were higher in summer than in winter. The NPP values at some sites shifted to negative values in summer, indicating the sites were carbon sources. The values of GPP m , TR and NPP for the tidal flats all increased significantly with increasing sediment mud content. The SEM results showed that the sediment mud content directly increased GPP m or indirectly increased GPP m via a compositional shift in benthic microalgae. The sediment mud content also directly increased TR or indirectly increased TR via increased organic matter content. The contribution of benthic microalgal and macrofaunal biomass to TR was relatively minor. This result suggests that primary production was stimulated mainly by the organic matter content rather than by increased microalgal biomass. With the integrated SEM framework, our results showed mechanistic evidence of how sediment mud content acted as a critical factor regulating carbon fluxes in unvegetated tidal flats.

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Translocation and distribution of mercury in biomasses from subtropical forest ecosystems: evidence from stable mercury isotopes - Yi Liu; Che-Jen Lin; Wei Yuan; Zhiyun Lu; Xinbin Feng (Acta Geochimica, 2021)

LMDS-1, a potential TrkB receptor agonist provides a safe and neurotrophic effect for early-phase Alzheimer’s disease - Chia-Hao Fan; Chia-Wei Lin; Hei-Jen Huang; Guey-Jen Lee-Chen; Ying-Chieh Sun; Wenwei Lin; Chiung-Mei Chen; Kuo-Hsuan Chang; Ming-Tsan Su; Hsiu Mei Hsieh-Li (Psychopharmacology, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Contribution of unvegetated tidal flats to coastal carbon flux - Wei‐Jen Lin; Jihua Wu; Hsing‐Juh Lin (Global Change Biology, 2020)
Unvegetated flats occupy a large area in the intertidal zone. However, compared to vegetated areas, the carbon sequestration of unvegetated tidal flats is rarely quantified, even though these areas are highly threatened by human development and climate change. We determined benthic maximum gross primary production (GPP m ), net primary production (NPP) and total respiration (TR) during emersion on seven tidal flats along a latitudinal gradient (from 22.48°N to 40.60°N) in winter and summer from 2012 to 2016 to assess the spatial and temporal variability of carbon dioxide flux. In winter, these processes decreased by 89%–104% towards higher latitudes. In summer, however, no clear trend was detected across the latitudinal gradient. Quadratic relationships between GPP m , NPP and TR and sediment temperature can be described along the latitudinal gradient. These curves showed maximum values of GPP m and NPP when the sediment temperatures reached 28.7 and 26.6°C respectively. TR increased almost linearly from 0 to 45°C. The maximum daily NPP across the latitudinal gradient averaged 0.24 ± 0.28 g C m −2 day −1 , which was only 10%–20% of the global average of NPP of vegetated coastal habitats. Multiplying with the global area of unvegetated tidal flats, our results suggest that the contribution of NPP on unvegetated tidal flats to the coastal carbon cycle is small (11.04 ± 13.32 Tg C/year). If the land cover of vegetated habitats is continuously degraded to unvegetated tidal flats, the carbon sequestration capacity in the intertidal zone is expected to reduce by at least 13.10 Tg C/year, equivalent to 1% of global carbon emissions from land‐use change.

Twist1 Plays an Anti-apoptotic Role in Mutant Huntingtin Expression Striatal Progenitor Cells - Wei-Ping Jen; Hui-Mei Chen; Yow-Sien Lin; Yijuang Chern; Yi-Ching Lee (Molecular Neurobiology, 2020)

Leveraging complementary computational models for prioritizing chemicals of developmental and reproductive toxicity concern: an example of food contact materials - Chun-Wei Tung; Hsien-Jen Cheng; Chia-Chi Wang; Shan-Shan Wang; Pinpin Lin (Archives of Toxicology, 2020)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

Sodium Metabisulfite: Effects on Ionic Currents and Excitotoxicity - Ming-Chi Lai; Te-Yu Hung; Kao-Min Lin; Pi-Shan Sung; Shyh-Jong Wu; Chih-Sheng Yang; Yi-Jen Wu; Jing-Jane Tsai; Sheng-Nan Wu; Chin-Wei Huang (Neurotoxicity Research, 2018)

Prototype Deep Brain Stimulation System with Closed-Loop Control Feedback for Modulating Bladder Functions in Traumatic Brain Injured Animals - En Jen; Chii-Wann Lin; Tsung-Hsun Hsieh; Yi-Chun Chiu; Tsung-Che Lu; Shih-Ching Chen; Meng-Chao Chen; Chih-Wei Peng (Journal of Medical and Biological Engineering, 2018)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Static Magnetic Field Increases Survival Rate of Thawed RBCs Frozen in DMSO-Free Solution - Yi-June Lo; Yu-Hwa Pan; Chun-Yen Lin; Wei-Jen Chang; Haw-Ming Huang (Journal of Medical and Biological Engineering, 2017)

Effects of Porphyromonas gingivalis on Titanium Surface by Different Clinical Treatment - Nominzul Batsukh; Sheng Wei Feng; Wei Fang Lee; Sy-Jye Leu; Pei-Yo Tsai; Kuo-Ning Ho; Che Tong Lin; Ching-Hua Su; Wei-Jen Chang (Journal of Medical and Biological Engineering, 2017)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

Polymorphisms of human 8-oxoguanine DNA glycosylase 1 and 8-hydroxydeoxyguanosine increase susceptibility to arsenic methylation capacity-related urothelial carcinoma - Chao-Yuan Huang; Yeong-Shiau Pu; Horng-Sheng Shiue; Wei-Jen Chen; Ying-Chin Lin; Yu-Mei Hsueh (Archives of Toxicology, 2016)

Quantitative measurement of Parkinsonian gait from walking in monocular image sequences using a centroid tracking algorithm - Sheng-Huang Lin; Shih-Wei Chen; Yu-Chun Lo; Hsin-Yi Lai; Chich-Haung Yang; Shin-Yuan Chen; Yuan-Jen Chang; Chin-Hsing Chen; Wen-Tzeng Huang; Fu-Shan Jaw; You-Yin Chen; Siny Tsang; et al. (Medical & Biological Engineering & Computing, 2016)

Six new metabolites produced by Colletotrichum aotearoa 09F0161, an endophytic fungus isolated from Bredia oldhamii - Yi Hsiao; Ming-Jen Cheng; Hsun-Shuo Chang; Ming-Der Wu; Sung-Yuan Hsieh; Ta-Wei Liu; Chu-Hung Lin; Gwo-Fang Yuan; Ih-Sheng Chen (Natural Product Research, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Classification of Benign and Malignant Breast Tumors in Ultrasound Images with Posterior Acoustic Shadowing Using Half-Contour Features - Zhuhuang Zhou; Shuicai Wu; King-Jen Chang; Wei-Ren Chen; Yung-Sheng Chen; Wen-Hung Kuo; Chung-Chih Lin; Po-Hsiang Tsui (Journal of Medical and Biological Engineering, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Two Frequent Mutations Associated with the Classic Form of Propionic Acidemia in Taiwan - Yen-Hui Chiu; Yu-Ning Liu; Wei-Ling Liao; Ying-Chen Chang; Shuan-Pei Lin; Chia-Chi Hsu; Pao-Chin Chiu; Dau-Ming Niu; Chung-Hsing Wang; Yu-Yuan Ke; Yin-Hsiu Chien; Kwang-Jen Hsiao; et al. (Biochemical Genetics, 2014)

Commonly Used Excipients Modulate UDP-Glucuronosyltransferase 2B7 Activity to Improve Nalbuphine Oral Bioavailability in Humans - Hong-Jaan Wang; Cheng-Huei Hsiong; Shung-Tai Ho; Min-Jen Lin; Tung-Yuan Shih; Pei-Wei Huang; Oliver Yoa-Pu Hu (Pharmaceutical Research, 2014)

Pemetrexed downregulates ERCC1 expression and enhances cytotoxicity effected by resveratrol in human nonsmall cell lung cancer cells - Ruey-Shyang Chen; Jen-Chung Ko; Hsien-Chun Chiu; Ting-Yu Wo; Yi-Jhen Huang; Sheng-Chieh Tseng; Huang-Jen Chen; Yu-Ching Huang; Yi-Jun Jian; Wei-Ting Lee; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Field Approaches to Measure Hg Exchange Between Natural Surfaces and the Atmosphere—A Review - Jonas Sommar; Wei Zhu; Che-Jen Lin; Xinbin Feng (Critical Reviews in Environmental Science and Technology, 2013)

Effect evaluation of shotcrete vegetation mulching technique applied to steep concrete-face slopes on a highway of Taiwan - Jen-Chen Fan; Chien-Lin Huang; Chih-Hsiang Yang; Kuo-Wei Liao; Wen-Wen Liao (Paddy and Water Environment, 2013)

Heat acclimation decreased oxidative DNA damage resulting from exposure to high heat in an occupational setting - Yung-Kai Huang; Che-Wei Lin; Chen-Chen Chang; Pai-Fen Chen; Chien-Jen Wang; Yu-Mei Hsueh; Hung-Che Chiang (European Journal of Applied Physiology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Availability of dopamine and serotonin transporters in opioid-dependent users—a two-isotope SPECT study - Tzung Lieh Yeh; Kao Chin Chen; Shih-Hsien Lin; I. Hui Lee; Po See Chen; Wei Jen Yao; Sheng-Yu Lee; Yen Kuang Yang; Ru-Band Lu; Mei-Hsiu Liao; Nan-Tsing Chiu (Psychopharmacology, 2012)

Carbon dynamics and community production in the Mississippi River plume - Xianghui Guo; Wei-Jun Cai; Wei-Jen Huang; Yongchen Wang; Feizhou Chen; Michael C. Murrell; Steven E. Lohrenz; Li-Qing Jiang; Minhan Dai; Justin Hartmann; Qi Lin; Randy Culp (Limnology and Oceanography, 2012)
Dissolved inorganic carbon (DIC), total alkalinity (TAlk), pH, and dissolved oxygen (DO) were determined in the Mississippi River plume during five cruises conducted in the spring, summer, and fall. In contrast to many other large rivers, both DIC and TAlk were higher in river water than in seawater. Substantial losses of DIC, relative to TAlk, occurred within the plume, particularly at intermediate salinities. DIC removal was accompanied by high DO, high pH, and nutrient depletion, and was attributed to high phytoplankton production. As a result, the carbonate saturation in the plume became much higher than in ocean and river waters. A mixing model was used to determine DIC removal. We provide evidence that the use of a two—end‐member (river and ocean) mixing model was valid during late summer and fall (low discharge period). However, for other periods we used salinity and TAlk to delineate a mixing model that included two river end members and an ocean end member. Net community production rates in the plume, estimated using a box model, peaked in the summer and were among the highest reported to date for large river plumes. In the summer and fall, biological production in the river plume consumed a majority of the available nutrients, whereas during the spring only a small fraction of the available nutrients were consumed in the plume. Biological production was the dominant process influencing pH and carbonate saturation state along the river—ocean gradient, whereas physicochemical dynamics of mixing played an important role in controlling the TAlk and DIC distributions of this large river plume.

Loudness dependence of auditory evoked potentials (LDAEP) correlates with the availability of dopamine transporters and serotonin transporters in healthy volunteers—a two isotopes SPECT study - I Hui Lee; Yen Kuang Yang; Po See Chen; Hui Chun Huang; Tzung Lieh Yeh; Ru-Band Lu; Nan-Tsing Chiu; Wei Jen Yao; Shih-Hsien Lin (Psychopharmacology, 2011)

BNIP3 induces IL6 and calcineurin/NFAT3 hypertrophic-related pathways in H9c2 cardiomyoblast cells - Yi-Jiun Weng; Wei-Wen Kuo; Chia-Hua Kuo; Kwong-Chung Tung; Chang-Hai Tsai; James A. Lin; Fuu-Jen Tsai; Dennis Jine-Yuan Hsieh; Chih-Yang Huang; Jin-Ming Hwang (Molecular and Cellular Biochemistry, 2010)

Static magnetic field exposure promotes differentiation of osteoblastic cells grown on the surface of a poly-l-lactide substrate - Sheng-Wei Feng; Yi-June Lo; Wei-Jen Chang; Che-Tong Lin; Sheng-Yang Lee; Yoshimitsu Abiko; Haw-Ming Huang (Medical & Biological Engineering & Computing, 2010)

E4BP4 is a cardiac survival factor and essential for embryonic heart development - Yi-Jiun Weng; Dennis Jine-Yuan Hsieh; Wei-Wen Kuo; Tung-Yuan Lai; Hsi-Hsien Hsu; Chang-Hai Tsai; Fuu-Jen Tsai; Ding-Yu Lin; James A. Lin; Chih-Yang Huang; Kwong-Chung Tung (Molecular and Cellular Biochemistry, 2010)

Hormone and sugar effects on rice sucrose transporter OsSUT1 expression in germinating embryos - Jia-Yi Chen; Shiang-Lin Liu; Wei Siao; Shu-Jen Wang (Acta Physiologiae Plantarum, 2010)

Atmospheric Aerosols over a Southwestern Region of Texas - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; Rafael Tadmor; T. C. Ho (Environmental Modeling & Assessment, 2009)

Single-Trial Analysis of Cortical Oscillatory Activities During Voluntary Movements Using Empirical Mode Decomposition (EMD)-Based Spatiotemporal Approach - Po-Lei Lee; Li-Zen Shang; Yu-Te Wu; Chih-Hung Shu; Jen-Chuen Hsieh; Yung-Yang Lin; Chi-Hsun Wu; Yu-Lu Liu; Chia-Yen Yang; Chia-Wei Sun; Kuo-Kai Shyu (Annals of Biomedical Engineering, 2009)

Atmospheric Aerosol over a Southeastern Region of Texas: Chemical Composition and Possible Sources - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; T. C. Ho (Environmental Modeling & Assessment, 2009)

Hypoxia-induced compensatory effect as related to Shh and HIF-1α in ischemia embryo rat heart - Jin-Ming Hwang; Yi-Jiun Weng; James A. Lin; Da-Tian Bau; Fu-Yang Ko; Fuu-Jen Tsai; Chang-Hai Tsai; Chieh-Hsi Wu; Pei-Cheng Lin; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2008)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Static Magnetic Fields Promote Osteoblast-Like Cells Differentiation Via Increasing the Membrane Rigidity - Kang-Hsuan Chiu; Keng-Liang Ou; Sheng-Yang Lee; Che-Tong Lin; Wei-Jen Chang; Chang-Chih Chen; Haw-Ming Huang (Annals of Biomedical Engineering, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Interleukin-18 gene polymorphism, but not interleukin-2 gene polymorphism, is associated with rheumatoid arthritis - Cheng-Chun Lee; Wei-Yong Lin; Lei Wan; Yuhsin Tsai; Ying-Ju Lin; Chang-Hai Tsai; Chung-Ming Huang; Fuu-Jen Tsai (Immunogenetics, 2007)

Pleomorphic extra-renal manifestation of the glomerular podocyte marker podocalyxin in tissues of normal beagle dogs - Wei-Ling Lin; Victor Fei Pang; Chen-Hsuan Liu; Jen-Yau Chen; Kuo-Fang Shen; Yu-Yu Lin; Chun-Ying Yu; Yung-Ho Hsu; Tzuu-Shuh Jou (Histochemistry and Cell Biology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Plant regeneration through shoot formation from callus of Areca catechu L. - Hsiang-Chih Wang; Jen-Tsung Chen; Shieh-Ping Wu; Mei-Chun Lin; Wei-Chin Chang (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Stability and Release Performance of a Series of Pegylated Copolymeric Micelles - Wen-Jen Lin; Lee-Wei Juang; Chi-Chang Lin (Pharmaceutical Research, 2003)

Plant regeneration through somatic embryogenesis from zygotic embryo-derived callus of Areca catechu L. (Arecaceae) - Hsiang-Chih Wang; Jen-Tsung Chen; Shieh-Ping Wu; Mei-Chun Lin; Wei-Chin Chang (In Vitro Cellular & Developmental Biology - Plant, 2003)

Natural Frequency Analysis of Periodontal Conditions in Human Anterior Teeth - Haw-Ming Huang; Sheng-Yang Lee; Ching-Ying Yeh; Mao-Sheng Wang; Wei-Jen Chang; Che-Tong Lin (Annals of Biomedical Engineering, 2001)